THE CONCEPT OF VOCATIONAL TRAINING OF FUTURE ELEMENTARY SCHOOL TEACHER TO INFORMATICS TRAINING - Sagan О.В. (Journal of Information Technologies in Education (ITE), 2016)
In the article the problem of professional training of future elementary school teacher to teach Informatics of junior schoolchild is revealed. Rapid development of information and communication technologies actualizes the high-quality requirements to informational competent members of society. Transformation of content of primary education, namely putting Informatics in the curricula, exerted impact on a social request of the elementary school teacher who doesn’t only thoroughly use means of information technologies, but also teaches Informatics as invariant discipline of elementary school. In work it is designed the methodical model of training of future elementary school teacher for teaching Informatics, its purpose is forming of methodology informational competence at future elementary school teacher, which is based on theoretical and practical readiness for teaching Informatics of junior schoolchild and is shown in abilities to organize of the teaching and educational process. Finding of a ratio of essential results of training in higher education institution and general and professional competences which were determined by means of expert evaluations became a basis of a substantial component of system. We design the expected result in the form of competence-based model of future elementary school teacher in a perspective of its preparation for the decision the informational and the methodologyinformational tasks of elementary school.